2019
DOI: 10.1080/19336896.2019.1590938
|View full text |Cite
|
Sign up to set email alerts
|

The insomnia phenotype in genetic Creutzfeldt–Jakob disease based on the E200K mutation

Abstract: The aim of the presented study was to reveal the frequency of insomnia spells in E200K genetic Creutzfeldt-Jakob disease (gCJD) patients. Clinical records of 22 subjects diagnosed with E200K gCJD were retrospectively reviewed. The patients w/wo insomnia (n = 4, 18%/n = 18, 82%) did not differ in age, sex and the duration of the symptomatic phase. Analysis of the clinical features in the groups yielded differences in the clinical signs in the early phase of the disorder, proportion of homozygotes (Met/Met) at c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Clinical and imaging differences between E200K gCJD and sCJD are not well understood. Some publications have reported insomnia and autonomic disturbance in patients with PRNP E200K mutations, which is not consistent with typical sCJD, and is more similar to fatal familial insomnia (FFI), another type of prion disease resulting from PRNP D178N mutations that impacts the thalamus ( Chapman et al, 1996 , Feketeova et al, 2019 , George et al, 2017 , Taratuto et al, 2002 ). Approximately 21% of the patients with E200K mutations had abnormally high thalamic signal on diffusion-weighted imaging (DWI), which indicated that the thalamus may be vulnerable in patients with gCJD with E200K mutations ( Kovacs et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical and imaging differences between E200K gCJD and sCJD are not well understood. Some publications have reported insomnia and autonomic disturbance in patients with PRNP E200K mutations, which is not consistent with typical sCJD, and is more similar to fatal familial insomnia (FFI), another type of prion disease resulting from PRNP D178N mutations that impacts the thalamus ( Chapman et al, 1996 , Feketeova et al, 2019 , George et al, 2017 , Taratuto et al, 2002 ). Approximately 21% of the patients with E200K mutations had abnormally high thalamic signal on diffusion-weighted imaging (DWI), which indicated that the thalamus may be vulnerable in patients with gCJD with E200K mutations ( Kovacs et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%